The addition of calcium oxide with different doses in the recirculation system to improve the abalone Haliotis squamata seed production - Supriyono, Eddy; Liubana, Debora Victoria; Budiardi, Tatag; Effendi, Irzal (Jurnal Akuakultur Indonesia, 2020)
Information about abalone growth is necessary to overcome the abalone culture sustainability. Water quality parameters are aspects that need to be reviewed, one of which is the calcium level in the water. The aim of this study was to determine the optimal calcium dose in recirculation system for abalone (Haliotis squamata) growth. The study was conducted with an experimental method with four treatments (calcium oxide with doses of 0, 15, 30, 45 mg/L) and three times replications. Abalone with 2.3 g body weight, 2.3 cm shell length, and 1.2 cm shell width was reared for 60 days in recirculation system and fed with Gracilaria verrucosa. The results showed that the best abalone treatment medium with the addition of calcium oxide to increase the abalone seed production was 15 mg/L CaO with 100% survival rate, 31.57±2.82% feed efficiency, and 0.56±0.06%/day specific growth rate. Keywords: Abalone, calcium, organ composition, production, recirculation ABSTRAK Informasi tentang pertumbuhan abalon diperlukan untuk mengatasi keberlanjutan budidaya abalon. Parameter kualitas air merupakan aspek yang perlu ditinjau. Kadar kalsium dalam air menjadi salah satu aspek yang dapat ditinjau.Tujuan dari penelitian ini adalah menentukan dosis kalsium optimal melalui sistem resirkulasi untuk pertumbuhan abalon Haliotis squamata. Penelitian ini dilakukan dengan metode eksperimental dengan empat perlakuan 3 ulangan penambahan CaO dengan dosis 0, 15, 30, dan 45 mg/L. Secara singkat, abalon dengan bobot badan 2,3 g, panjang cangkang 2,3 cm dan lebar cangkang 1,2 cm dipelihara selama 60 hari dengan sistem resirkulasi dan diberi makan dengan Gracilaria verrucosa. Hasil penelitian menunjukkan bahwa media perlakuan abalon dengan penambahan kalsium oksida terbaik untuk meningkatkan produksi abalon adalah CaO 15 mg/L dengan tingkat kelangsungan hidup 100%, efisiensi pakan 31,57 ± 2,82 %, dan laju pertumbuhan spesifik harian 0.56 ± 0.06%/hari. Kata kunci: Abalon, kalsium, komposisi organ, produksi, resirkulasi